Experimental Models of Endotheliopathy: Impact of Shock Severity. Issue 5 (May 2018) - Hofmann, Nikolaus; Zipperle, Johannes; Jafarmadar, Mohammad; Ashmwe, Mostafa; Keibl, Claudia; Penzenstadler, Carina; Ponschab, Martin; Jafarmadar, Behnaz; Redl, Heinz; Bahrami, Soheyl; Schöchl, Herbert
ABSTRACT: Background: Hemorrhagic shock (HS) followed by resuscitation is often associated with sympathoadrenal activation (SAA) and endothelial damage (ED). Objective: We aimed to evaluate the impact of HS alone on the magnitude of SAA and consecutive ED, and to characterize potential targets for a standardized and reproducible model of HS-induced endotheliopathy in rats. Methods: Rats were subjected either to a volume-controlled HS (40% of total blood volume: v-HS group) or to a laboratory-guided HS (l-HS) targeting base deficit (BD) more than 5.5 mmol/L and/or lactate more than 2.2 mmol/L using a pressure-controlled volume loss. Results: At the end of shock, mean arterial pressure was significantly higher in the v-HS than the l-HS group (36 ± 5.6 vs. 30 ± 3.0 mmHg; P < 0.01). Base deficit and lactate were higher in l-HS than the v-HS group (BD: 9.5 ± 2.5 vs. 3.0 ± 1.0 mmol/L; P < 0.001; lactate: 4.1 ± 1.3 vs. 1.6 ± 0.6 mmol/L; P < 0.001). sVEGFR-1 and syndecan-1 were approximately 50% higher in the l-HS than the v-HS group (% changes vs. baseline: 160 ± 10 vs. 116 ± 36; P < 0.01; 170 ± 37 vs. 113 ± 27; P < 0.001). Adrenaline was 2-fold higher in l-HS than the v-HS group (1964 ± 961% vs. 855 ± 451%; P < 0.02, respectively). Moreover, linear regression analysis revealed an independent association of shock severity BD with syndecan-1 (rho = 0.55, P = 0.0005), sVEGFR1 (rho = 0.25, P < 0.05), and adrenaline (rho = 0.31, P = 0.021). Conclusions: Our findings indicate that ED has already occurred during HS without reperfusion; intensity is strongly related to the severity of HS and consecutive SAA; and severity may appropriately be targeted and standardized in a HS model controlled by biological endpoints such as BD and/or lactate.